PENGEMBANGAN KAWASAN WONOREJO MENJADI OBYEK WISATA “TIRTA AGRO FOREST WISATA” GUNA OPTIMALISASI PEMANFAATAN WADUK BAJULMATI DI KABUPATEN SITUBONDO DAN BANYUWANGI - Yohanes Nangameka (Relawan Jurnal Indonesia, 2017)
Wonorejo area is located at the east end of Situbondo Regency bordering with Banyuwangi Regency which has great potential in the field of tourism. There are three potentials that are quite prominent, they are the potential of water tourism, agro tourism and forest tourism. However, these three potentials are not yet fully utilized. With the operation of the Bajulmati reservoir, it will increase all of its potentials, making it more attractive for tourism development. The potentials of tourism in this region include: 1). Food agriculture and horticulture; 2). Plantation area; 3). Forest area, 4). Aquatic area, and 5). Sea area. The development of these areas into a tourist area still faces problems, such as: 1). Differet views that have not been unified to see that the attractions of Wonorejo region can be used as Tourism Object